A Limiting Joint-Choice Model for Discrete and Continuous Housing Characteristics - Blakley, Paul; Ondrich, Jan (The Review of Economics and Statistics, 1988)
A simultaneous discrete and continuous random utility model for housing demand is presented. Household utility depends on three characteristics of hou sing: a discrete number of bedrooms and continuous measures of hous-i ng quality and distance to the central business district. Empirical r esults for a sample of renter households from San Francisco are compa red for a univariate structure in which each choice variable has its own utility or disutility function, a simultaneous structure assuming a discrete-continuous analog of the independence of irrelevant alter natives, and one for which this assumption is relaxed. The results in dicate that the third structure is most appropriate. Copyright 1988 by MIT Press.